Purification of plasmid DNA vectors by aqueous two-phase extraction and hydrophobic interaction chromatography - Trindade, Inês P. (2005)
The current study explores the possibility of using a polyethyleneglycol(PEG)/ammonium sulphate aqueous two-phase system (ATPS) as an early step in a process for the purification of a model 6.1 kbp plasmid DNA (pDNA) vector. Neutralised alkaline lysates were fed directly to ATPS. Conditions were selected to direct pDNA towards the salt-rich bottom phase, so that this stream could be subsequently processed by hydrophobic interaction chromatography (HIC). Screening of the best conditions for ATPS extraction was performed using three PEG molecular weights (300, 400, 600) and varying the tie-line length, phase volume ratio and lysate load. For a 20 % (w/w) lysate load, the best results were obtained with PEG 600 using the shortest tie-line (38.16 % w/w). By further manipulating the system composition along this tie-line in order to obtain a top/bottom phase volume ratio of 9.3 (35 % w/w PEG 600, 6% w/w NH4)2SO4), it was possible to recover 100 % of pDNA in the bottom phase with a 3-fold increase in concentration. Further increase in the lysate load up to 40 %(w/w) with this system resulted in a 8-fold increase in pDNA concentration, but with a yield loss of 15 %. The ATPS extraction was integrated with HIC and the overall process compared with a previously defined process that uses sequential precipitations with isopropanol and ammonium sulphate prior to HIC. Although the final yield is lower in the ATPS-based process the purity grade of the final pDNA product is higher. This shows that it is possible to substitute the time-consuming two-step precipitation procedure by a simple ATPS extraction.